Un sistema per la gestione dell'affidabilità e dell'interpretazione dei dati archeologici : percezione e potenzialità degli small finds : il caso studio di Festòs e Haghia Triada - Figuera, Marianna, (Praehistorica Mediterranea ;, 2020)
This work aims to identify methodological problems associated with the digital management of archaeological data and to introduce viable solutions that embrace interpretative aspects and the reliability concept. A prototype system is presented, managing small finds data from early 20th century excavations at Phaistos and Ayia Triada.